Ameloblastic Fibroodontoma: Uncommon Case Presentation in a 6-Year-Old Child with Review of the Literature - Anshad Mohamed Abdulla; G. Sivadas; L. K. Surej Kumar; C. S. Sheejith Hari Peeceeyen; Vaishnavi Vedam (Case Reports in Medicine)
Ameloblastic fibroodontoma is a benign mixed odontogenic neoplasm considered in patients with asymptomatic swelling and unerupted teeth that exhibit histologic features between ameloblastic fibroma and complex odontoma. Radiographically, this lesion appears as radiolucency admixed with focal radio opaque masses of irregular shapes and sizes. This lesion is confirmed by the presence of proliferating odontogenic epithelium, ectomesenchyme, and dental hard tissue formation on pathological analysis supplementing clinical and radiographic findings. As this tumour is less commonly seen in routine clinical practice, ameloblastic fibroodontoma with detailed orofacial features and periodic approach to its diagnosis is discussed. This paper reports a case of ameloblastic fibroodontoma of the mandible in a 6-year-old male patient with an uncommon case presentation and review of the literature.